Design and construction of concrete floors - Garber, G. (George) (Burlington, MA : Elsevier/Butterworth-Heinemann, 2006)
Outlines the key principles needed for the production of a good floor. This book covers: uses of concrete floors; structural design; concrete used specifically for floors; cracks and joints; and floor surface properties. It demonstrates how to successfully design and build concrete floors by drawing from a range of global experience
1. Introduction: Thinking about Floor DesignPart 1: The uses of concrete floors2. Non-Industrial Floors3. Warehouse Floors4. Factor and Special FloorsPart 2: Structural Design5. Structural Design of Ground-Supported Floors6. Structural Design of Suspended FloorsPart 3: Concrete Floors7. Properties of Plastic Concrete8. Properties of Hardened Concrete9. The Components of Concrete10. Mix Design and Mixing11. Transporting and Placing Concrete12. CuringPart 4: Joints and Cracks13. Cracks14. Curling15. Joints16. Crack Control in Ground-Supported FloorsPart 5: The Floor Surface17. Floor Finishing18. Concrete Toppings19. Surface Regularity20. Resistance to Wear21. Resistance to Chemical Attack22. Preparation for Coatings, Toppings and FloorcoveringsGlossary
Includes bibliographical references (p. [365]-367) and index.
Keywords: Floors, Concrete -- Design and construction